Analisis Pertimbangan Hakim dalam Putusan Tindak Pidana Pencurian dengan Pemberatan di Pengadilan Negeri Medan - Mantasia Hasibuan; Parlaungan Gabriel Siahaan; Dewi Pika Lbn Batu; Ida Nurjana Tamba; Fariz Aditya; Florensia Silaban (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study aims to examine the judge's considerations in rendering decisions in aggravated theft cases at the Medan District Court, with an emphasis on the balance between legal and non-legal aspects in realizing substantive justice. The issue of disparate sentencing that frequently arises is the main background of this study. The methods used are an integrated normative legal approach and an empirical legal approach. The normative approach is used to examine the provisions of Article 363 of the Criminal Code (KUHP) and the legal principles that govern the judge's considerations, while the empirical approach is carried out through direct observation of the trial process and analysis of the judge's decision. The results of the study indicate that the judge in case Number 1110/Pid. B/2025/PN Medan not only complied with legal aspects such as fulfilling the elements of the crime, evidence, and the application of the principle of legality, but also considered non-legal aspects such as the socio-economic conditions, age, and motives of the defendant. These considerations demonstrate the application of the principles of criminal individualization and proportional justice. In addition, the judge also considered moral values ​​and social benefits in his decision, which is in line with Gustav Radbruch's theory of three basic legal values: justice, legal certainty, and utility. This study concludes that the thinking patterns of judges at the Medan District Court reflect a shift toward substantive and restorative justice paradigms. It is recommended that the Supreme Court strengthen integrated sentencing guidelines to avoid disparities in sentencing and encourage the adoption of a rehabilitative approach for offenders with low economic motivations.